2000
DOI: 10.1152/ajplung.2000.279.1.l43
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain-induced proliferation and signaling in pulmonary epithelial H441 cells

Abstract: Pulmonary epithelial cells are exposed to mechanical strain during physiological breathing and mechanical ventilation. Strain regulates pulmonary growth and development and is implicated in volutrauma-induced fibrosis. The mechanisms of strain-induced effects are not well understood. It was hypothesized that mechanical strain induces proliferation of pulmonary epithelial cells and that this is mediated by signals initiated within seconds of strain. To test this hypothesis, human pulmonary adenocarcinoma H441 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 44 publications
3
48
2
Order By: Relevance
“…This is supported by the fact that mechanical stretch has been shown to activate ERK and JNK in cardiac myocytes [25], mesangial cells [26], melanocytes [27], pulmonary endothelial cells [28] and L929 cells [29]. Activation of ERK-1/2 (p42/p44) was reported within 10 min of 20% elongation of H441 pulmonary epithelial cells [30]. In A549 cells, it was shown that 15% strain activated JNK (stress-activated protein kinase) within 30 min and p38 kinase at later time points (2 h), whereas ERK-1/2 was not activated [31].…”
Section: Discussionmentioning
confidence: 89%
“…This is supported by the fact that mechanical stretch has been shown to activate ERK and JNK in cardiac myocytes [25], mesangial cells [26], melanocytes [27], pulmonary endothelial cells [28] and L929 cells [29]. Activation of ERK-1/2 (p42/p44) was reported within 10 min of 20% elongation of H441 pulmonary epithelial cells [30]. In A549 cells, it was shown that 15% strain activated JNK (stress-activated protein kinase) within 30 min and p38 kinase at later time points (2 h), whereas ERK-1/2 was not activated [31].…”
Section: Discussionmentioning
confidence: 89%
“…Several cells respond to mechanical forces by activating MAPK pathways, but little is known about how mechanical stimuli are converted into biochemical signals in AEC (18). Mechanical stress has been shown to stimulate ERK1/2 in endothelial cells (11,29), cardiac myocytes (41), vascular smooth muscle cells (VSMC) (39), and in H441 cells (3). Another component of the MAPK family, the stressactivated protein kinase/c-Jun NH 2 -terminal kinase (SAPK/JNK), is activated by cyclic stretch in A549 cells (21), and stretching these cells induces an interleukin-8 release (33).…”
mentioning
confidence: 99%
“…In addition, ERK phosphorylation mediated by different ECM-cell interactions in fetal lung development may not be limited to type II cell differentiation. In fact, strain-induced ERK activation influences cell proliferation in pulmonary epithelial H441 cells (6) and osmotic stress and apoptosis in adult type II cells (11). These studies suggest that strain-induced ERK activation, via ECM-cell interactions, may participate in a variety of cellular processes that are important for fetal lung development, in addition to differentiation.…”
Section: Discussionmentioning
confidence: 90%